2020
DOI: 10.1038/s41598-020-58175-4
|View full text |Cite
|
Sign up to set email alerts
|

Specialized structures on the border between rhizocephalan parasites and their host’s nervous system reveal potential sites for host-parasite interactions

Abstract: Rhizocephalan barnacles are a unique group of endoparasitic crustaceans. In their extreme adaptation to endoparasitism, rhizocephalan adults have lost almost all features of their free-living relatives but acquired an outstanding degree of control over the body of their hosts (mostly decapods). The subtle influence exercised by rhizocephalans on the physiology, morphology and behaviour of their hosts is a vivid example of the most intimate host-parasite interactions but their mechanisms are very poorly known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…We also observed an unanticipated difference between the two interna samples from the host midgut and thoracic ganglia ( fig. 5 ), supporting recent reports showing the differing morphology and activity of rootlets in the rhizocephalan species Peltogasterella gracilis ( Miroliubov et al 2020 ) and Sacculina pilosella ( Lianguzova et al 2021 ). These studies describe morphological differentiation of those rootlets in contact with host nerve chords and indicate that these sites allow for humoral interactions between the parasite and host.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…We also observed an unanticipated difference between the two interna samples from the host midgut and thoracic ganglia ( fig. 5 ), supporting recent reports showing the differing morphology and activity of rootlets in the rhizocephalan species Peltogasterella gracilis ( Miroliubov et al 2020 ) and Sacculina pilosella ( Lianguzova et al 2021 ). These studies describe morphological differentiation of those rootlets in contact with host nerve chords and indicate that these sites allow for humoral interactions between the parasite and host.…”
Section: Resultssupporting
confidence: 86%
“…5 ). Recent studies with other Rhizocephala have shown that rootlets in different regions of the host take on different characteristics ( Miroliubov et al 2020 ). The 1870 differentially expressed genes (DEGs) included 1012 with conserved protein domains and we were able to assign Gene Ontology (GO) terms to 661 of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The body of an adult rhizocephalan female is represented by the interna, a system of hollow, ramifying rootlets infiltrating the body cavity of the host (also crustaceans, usually decapods), and the externa, a sac-like body protruding outside the host. The interna is responsible for absorbing nutrients from the host hemolymph and their transportation to the externa 1 as well as for interactions with the host 3 , 4 . The externa is a temporary structure thought to be an organ of sexual reproduction 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These parasites can take control of the molting cycle of the hosts, change their metabolism, behaviour, and even body shape 2 , 10 20 . Specialized sites responsible for host-parasite interactions have recently been described 3 , 4 , with a network of the host’s neurons enlacing the rootlets of the parasite, but the molecular mechanisms of these interactions remained enigmatic. The authors suggested that the parasite may emit some signal molecules attracting the growth of the host’s neurons 3 .…”
Section: Introductionmentioning
confidence: 99%